Comparison of sedation scores after nebulized and intravenous Midazolam in children - M., Mounika; R., Aswathy; A., Shriyan; A. O., Roshan (International Journal of Contemporary Pediatrics, 2018)
Background: An efficacious, reliable, and non-invasive route of administration for midazolam, a drug used for sedation and pre-anesthetic medication, would have obvious advantages. This study compares the sedation achieved by nebulized route and intravenous route as procedural sedation. Methods: A randomized double-blinded interventional study was designed to compare the effect of nebulized midazolam with intravenous midazolam as a sedative medication in 86 children undergoing imaging procedures like CT scan, MRI scan, EEG. Ramsay sedation scores and parameters of cardiovascular and respiratory function were measured over 20 min and summarized Results: The mean sedation score in both groups was comparable at baseline, 10 minutes and 20 minutes with p values of 0.1, 0.1, 0.09 respectively. Parameters of cardiovascular and respiratory function were comparable in both the groups. Conclusion: Present study showed that nebulized midazolam when given at a higher dose of 1 mg/kg was found to be as potent as intravenous midazolam, opening up a door for a sedative which is easier to administer, has better acceptance with lesser complication.